Development and Evaluation of Felbamate Loaded Solid Lipid Nanoparticles - Ramanuj Prasad Samal (Journal of Global Pharma Technology, 2020)
Solid lipid nanoparticles (SLN’s) or lipid nano particles is typically sphere-shaped, with an average diameter of 1nm to 1000nm. They are alternative carrier systems to tradition colloidal carriers, such as, emulsions, liposomes, and polymeric micro and nanoparticles. The main aim of the current research work is to prepare and optimize the Felbamate loaded solid lipid nanoparticles using by placket and burman design of experiments. SLN’s were prepared by microemulsion technique. Based on preliminary experiments and on literature, the influence of independent variable parameters selected were lipid (X1), surfactant (X2), and co-surfactant concentration(X3),aqueous phase volume(X4),magnetic stirrer rate (X5), probe sonication duration (X6), volume of beaker used for sonication (X7), volume of cold aqueous phase (X8) on the dependent variable such as average particle size (Y1) was studies. Other parameters, i.e., magnetic stirrer rate and probe sonication duration were not having a significant impact on particle size and their levels were kept constant for all the experiments. Magnetic stirrer rate has an impact on particle size and was included in the design. It was concluded from the study that the composition prepared with lipid concentration of 50 mg, surfactant concentration of 75 mg, Co-surfactant concentration of 0.75 ml, aqueous phase volume of 5 ml, magnetic stirring speed of 400 rpm, probe sonication duration 30 minutess, volume of beaker used for sonication 500 ml and volume of cold aqueous phase 30 ml has shown the smallest particle size of 165 nm